The Relation between Quality and Innovation in the Context of Agricultural Tractors Certification in Mexico - Reyes Chacón, David Arturo; Rivera González, Gibrán; Ayala Garay, Alma Velia; Cadena López, Aydé; Ángeles Tovar , Luis Canek (Unidad Editorial UPTC, 2023)
The goal of this paper is to analyze the relation between quality and innovation within the context of the certification of agricultural tractors in Mexico. To accomplish this goal, qualitative research with methodological triangulation was conducted through official documentation, semi-structured interviews, observation, and questionnaires conducted within manufacturing and distribution companies with internationally certified tractors. Through a relational model, we argue that quality indirectly contributes to innovation, due to the existence of an intermediate variable which shapes the relation between quality and innovation. This intermediate variable is integrated by components such as the ecosystem of Science, Technology and Innovation, organizational culture, marketing and brand value, exploitation of knowledge, human resources, R&D, as well as adaptability and R&D projects. A better performance of the variables of manufacturing enterprises over distribution companies allows us to show how the components of innovation boosting result in learning processes which in turn promote innovation. We conclude that the components of quality do not provide direct results in innovation, instead, they encourage and reinforce the intermediate components that drive it. We consider that the findings could be useful for other enterprises and industries. JEL Codes: O32, L15, Q1, Q13, Q16, L62 Received: 11/07/2023.  Accepted: 31/08/2023.  Published: 09/11/2023.